Predictors of Insulin Resistance and Liver Steatosis in the Miami Adult Studies on HIV (MASH) Cohort. (29th May 2020) - Teeman, Colby; Hernandez, Jacqueline; Huang, Yongjun; Rodriguez, Jose Bastida; Gonzalez, Nicholas; Tamargo, Javier; Johnson, Angelique; Jasmin, Jupshy; Seminario, Leslie; Zarini, Gustavo; Martinez, Sabrina Sales; Campa, Adriana; et al.
Abstract: Objectives: Immune activation is central to developing insulin resistance and is implicated in the pathophysiology of liver steatosis. People living with HIV (PLWH) have elevated biomarkers of immune activation, which may play a role in faster development of insulin resistance and liver steatosis. The objective of this study was to examine if HIV status and immune activation are related to insulin resistance and liver steatosis. Methods: Demographic and anthropometric data on MASH cohort participants were obtained. Insulin resistance was estimated using the triglyceride-glucose (TyG) index from fasting blood. HIV status was abstracted from participants' medical records. Immune activation biomarkers soluble CD163 (sCD163), sCD27, sCD14, and monocyte chemoattractant protein (MCP-1) measured with multiplex flow cytometry in Dr. Sherman's laboratory. High sensitivity C-Reactive Protein (hsCRP), measure of inflammation, was determined by LabCorp. Liver steatosis was defined as liver fat >3.5% obtained with magnetic resonance elastography scans. Statistics included descriptive analysis, Mann-Whitney tests, multivariate linear, and logistic regressions, controlled for age, sex, and BMI. Results: Of the 712 participants (age 54.24 ± 7.48 years), 336 were PLWH with suppressed viral load, and 376 were uninfected healthy participants. PLWH had higher levels of sCD27 ( P  = 0.003) and MCP-1 ( P  = 0.034) than uninfected participants. Multiple linear regressions showed HIV status and sCD163 were independently associated with higher insulin resistance (HIV status b = 0.130, P  = 0.014, sCD163 Multiple logistic regressions showed higher levels of sCD163 (OR = 1.097, 95% CI: 1.01–1.19, P  = 0.032) and insulin resistance (OR = 7.126, 95% CI: 2.59–19.58, P  < 0.001) were significant predictors of liver steatosis. HIV status, sCD14, sCD27, hsCRP, or MCP-1 were not related to liver steatosis. Conclusions: These results indicate that HIV infection and sCD163, a marker of immune activation, are independent predictors of insulin resistance, and sCD163 was associated with greater odds of liver steatosis. Lifestyle interventions and anti-inflammatory agents aimed at reducing insulin resistance and immune activation in PLWH may help to reduce the risk of liver steatosis and other co-morbidities. Funding Sources: Grant Number: U01DA040381.